(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper addresses the problem of calculating vegetation indices for agricultural crops. Vegetation indices serve as powerful tools for assessing the health and abundance of vegetation in a given area. Using complex mathematical formulas, these indices leverage a wealth of remote sensing data, particularly satellite imagery, to provide invaluable information on the overall health and productivity of vegetation.